Hotel Council of San Francisco and corporate social responsibility (CSR) - Collins, Michael D.; Jones, David L., active 2017; Millar, Michelle (London : International CHRIE, 2017)
The Hotel Council of San Francisco is concerned that aggressive panhandling and other street behavior in areas of the city frequently visited by tourists may tarnish San Francisco's image as a world-class tourism and meetings destination. Meanwhile, San Francisco's hotel industry is enjoying record financial success. Consequently, the Hotel Council is striving to formulate a strategy to address their concerns before this success is derailed. This case study provides insight relative to how the hotel industry interfaces with the local community including information on the economic impact of hotels, tax revenues generated by hotels, and the quality of employment opportunities provided, which illustrate hotels efforts to be good corporate citizens.
Originally Published InCollins, M. D., Millar, M., & Jones, D. L. (2017). Hotel Council of San Francisco and corporate social responsibility (CSR). Journal of Hospitality & Tourism Cases, 5(3), 44–56.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hotel Council of San Francisco -- Case studies; Social responsibility of business -- California -- San Francisco -- Case studies; Hospitality industry -- Social aspects -- California -- San Francisco -- Case studies